Equitation science - McGreevy, Paul 1964-; Christensen, Janne Winther; Borstel, Uta Konig von; McLean, Andrew (Hoboken, New Jersey Wiley, 2018)
Equitation Science, second edition incorporates learning theory into ethical equine training frameworks suitable for riders of any level and for all types of equestrian activity. Written by international experts at the forefront of the development of the field, the welfare of the horse and rider safety are primary considerations throughout. This second edition reflects the most recent advance in the discipline, and feature a new chapter on research methods. Drawing together the principles of th is emerging field, discussion centers around how horses thing and learn, before exploring how to train, ride or compete with them in as fair a manner as possible and in ways that acknowledge their natural behavior. The welfare consequences of training and competing horses under different protocols are explored. Equitation Science, second edition is suitable for undergraduate and postgraduate students of equine science, equine studies or equine behavior. The text is also an invaluable reference for equine veterinarians, equine behavior counselors and, of course, horse riders and riding instructors.--COVER.
Introduction - The fascination with horses and learning -- Ethology and cognition -- Anthropomorphism and the human-horse relationship -- Non-associative learning (attractive stimuli) -- Associative learning (aversive stimuli) -- Applying learning theory -- Training -- Horses in sport and work -- Apparatus -- Biomechanics -- Unorthodox techniques -- Stress and fear responses -- Ethical equitation -- Research methods in equitation science -- The future of equitation science.
"This book is accompanied by a companion website"--Page vi.
Revised edition of: Equitation science / Paul McGreevy and Andrew McLean. 2010.
Includes bibliographical references and index.
Keywords: Horses -- Training; Horsemanship; Horses -- Psychology